FORMATION OF A DIGITAL CULTURE OF FUTURE SPECIALISTS IN THE FIELD OF PHYSICAL EDUCATION AND SPORTS - G. R. Muratova (Research Focus International Scientific Journal, 2025)
Abstract The rapid digital transformation of society necessitates the integration of digital competencies into the professional training of future specialists in physical education and sports. This article examines the theoretical foundations and practical approaches to the formation of digital culture among students in higher educational institutions. The study analyzes the role of modern digital technologies in enhancing educational effectiveness, improving methodological support, and fostering innovative pedagogical practices. Based on the conducted research, key components of digital culture in the context of physical education and sports are identified, including information literacy, digital communication skills, and the ability to apply technological tools in professional activities.